Learning occupational safety through gamification: A randomized controlled field trial - La Torre, Giuseppe; Capece, Guendalina; Shaholli, David; Nicolì, Francesca; Mannocci, Alice (Annali di Igiene Medicina Preventiva e di Comunità, 2026)
Background. Traditional health and safety training often fail to engage workers effectively. Gamification has emerged as a promising strategy to enhance motivation and learning outcomes. This study aimed to assess the effectiveness of a gamified training course in improving occupational health and safety knowledge. Methods. A randomized controlled field trial was conducted with 77 participants. Participants were divided into two groups: an experimental group (EG) and a control group (CG). The intervention, titled “Let’s play to 626!” consists of a one-day course comprising a seminar and gaming session. The participants were assessed using an internally validated Q626 questionnaire at baseline (T0) and after the intervention (T1), with a knowledge score was computed ranged from to 0-15. Descriptive statistics, paired sample tests, and regression analyses were used to analyse the data. Results: The internal reliability of the Q626 tool was moderate, with Cronbach’s α of 0.723. The results indicated a significant improvement in Q626 scores for both the experimental group (EG) and the control group (CG) at T1 compared to T0 (p<0.001; meanEGT1=10.8, SD=1.9; meanCGT1=10.0, SD=2.7). Discussion: The gamification session showed a positive effect on knowledge enhancement. Indeed, gamified training in occupational health and safety not only enhances learning retention and engagement but also represents a cost-effective solution to reduce the probability of workplace incidents. Future studies should explore the long-term impact of gamified learning on occupational health and safety training.